High Torque and Increased Wear Redefine Gearbox Longevity in Electric Motors: Torsi Tinggi dan Peningkatan Keausan Mendefinisikan Ulang Umur Panjang Gearbox pada Motor Listrik - Yudistira, Muhammad Dwi Andika; Fahruddin, A’rasy (Procedia of Engineering and Life Science, 2024)
This study explores the accelerated wear of gearboxes driven by electric motors compared to gearboxes in combustion engines, highlighting the important role of lubrication quality. The continuous operation of sugarcane processing machines requires durable gearboxes, especially under the high torque load of electric motors. By analyzing gearbox wear through standard load tests and various lubricant qualities, the findings reveal that superior lubricants significantly reduce wear. These results not only demonstrate the need for customized gearbox designs for electric motors, but also show that improvements in lubrication practices can extend gearbox life and increase efficiency in industrial applications globally. Highlights: Continuous operation vital for production targets. Electric motorbike gearboxes need frequent maintenance. Quality lubrication crucial for gearbox longevity. Keywords: Gearbox, Grind, Sugar Factory